Performance enhancement of energy saving and machining characteristic in electrical discharge machining on magnesium alloy: A review - Norizwan, Juraimi; Arman, Shah; Mas Ayu, Hassan; Mazlan, Mohamed; Kenzhaliyev, Bagdaulet; Mohammad, Khairudin; R., Daud; Abdelkarim, Hassan Abdelwahab (Akademi Baru, 2020)
Magnesium alloys have been widely used in biodegradable applications due to it tends to corrode inside the human body and combined with its initial mechanical property. Current research revealed that the structural stability of the implant is disturbed and lost rapidly due to the increased rate of degradation of magnesium inside the human body. Because of that, non-traditional machining method such as electrical discharge machining (EDM) die sinking process is implemented to create an intricate form with a high tolerance of magnesium alloy. The advantages of EDM are that it allows a versatile adaption of implant behaviour in machining complex 3D structures along with high corrosion resistant properties of electrochemical surface treatment. Various material types with different parameters are investigated to determine the influence of input process parameters on the energy saving, and machining characteristics included surface roughness, material removal rate, and tool wear rate. In addition to improving the machining performance especially in energy-saving, input on the machining parameter needs to be considered due to interaction with added conductive particles which would affect the size of discharge energy. The objective of this paper is to summarize the findings in research of EDM’s energy-saving and machining characteristics on magnesium alloy and to explore challenging issues that need to be resolved for future references and recommendations.